1943
DOI: 10.1084/jem.77.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Hypoalbuminemia Produced by Protein-Deficient Diets

Abstract: Plasma transfusions are often used clinically to correct hypoproteinemia resulting from malnutrition although the results are often disappointing in the severe cases. It seemed advisable, therefore, to study experimentally the effect of intravenous plasma in dogs depleted by a non-protein diet which has been shown by Weech (1) and ourselves (2) to produce a rapid fall in the albumin fraction of the blood. Holman, Mahoney, and Whipple (3) were the first to study the metabolic effect of plasma transfusions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1944
1944
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Parenterally injected albumin and plasma proteins disappear rapidly from the blood stream (1,21), but repeated injections are followed by an appreciable and readily detectable increase in the total circulating plasma proteins, as reported here and by others (5,10,12). It is clear that roughly 24 to 46 per cent of the protein retained in our subjects could be accounted for by the albumin increase in the blood plasma (Table II, hydrolysate).…”
Section: Discussionsupporting
confidence: 80%
“…Parenterally injected albumin and plasma proteins disappear rapidly from the blood stream (1,21), but repeated injections are followed by an appreciable and readily detectable increase in the total circulating plasma proteins, as reported here and by others (5,10,12). It is clear that roughly 24 to 46 per cent of the protein retained in our subjects could be accounted for by the albumin increase in the blood plasma (Table II, hydrolysate).…”
Section: Discussionsupporting
confidence: 80%
“…E. G. (see Figure 2) who received slightly more than 8 of the urine began to increase and rose slowly but progressively until the experimental period was terminated. In only one instance, however (the case of G. V.), did the urinary nitrogen become so great as to produce a negative nitrogen balance.…”
Section: Nitrogen Balancementioning
confidence: 99%
“…The opinions and conclusions are those of the authors and do not necessarily reflect the policy of the National Blood Program. 8 Henry C. Buswell Fellow in Internal Medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten years ago, animal studies showed that homologous plasma proteins were retained during the several days of infusion. There was controversy as to whether or not a subsequent loss of equivalent nitrogen occurred (1)(2)(3). Recent studies in Whipple's laboratory (4) have shown, however, that the protein balance of dogs may be maintained for three months with plasma as the sole source of nitrogen.…”
mentioning
confidence: 99%